Psychological Problems During The COVID-19 Pandemic Among Medical Students : A Cross-Sectional Study - Putri Rizki Amalia Badri; Rury Tiara Oktariza (Research Centre of Inorganic Materials and Complexs, 2021)
The pandemic of COVID-19 gave a great impact on college students learning activity, especially medical students. Thus, they may become vulnerable to have psychological problems such as anxiety, depression, and stress. The study aimed to investigate anxiety, depression, and stress rates among medical students during the pandemic of COVID-19 and the affecting factors. This cross-sectional study used DASS questionnaire online survey. 312 medical students, a total sampling in Muhammadiyah Palembang University participated in this study. The univariate analysis was used to determine the level of psychological problems while the bivariate analysis was carried out to determine the affecting factors. The study findings showed that 50.6% of the students reportedly had anxiety (12.2 % mild, 17.3% moderate, 10.9% severe, 10.3% very severe), 33% of the students had depression (13.5% mild, 11.9% moderate, 3.8% severe, 3.8% very severe), and 22.4% of the students had stress (10.6% mild, 9.3% moderate, 5.1% severe, 1.3% very severe). There were no differences between gender for anxiety, depression and stress (p=0.335, p=0.261, p=0.134 respectively). Junior students were more anxious than senior students (p=0.015). More than half of medical students experienced anxiety with moderate anxiety mostly during the COVID-19 pandemic, and junior students were more likely to suffer anxiety.